2019
DOI: 10.1016/j.neuron.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic TDP-43 De-mixing Independent of Stress Granules Drives Inhibition of Nuclear Import, Loss of Nuclear TDP-43, and Cell Death

Abstract: Graphical Abstract Highlights d Transient stress induces long-lasting phase separation of cytoplasmic TDP-43 d Formation/maintenance of phase separated TDP-43 is independent of stress granules d Phase-separated TDP-43 inhibits nuclear transport by demixing importin-a and Nup62 d Cytoplasmic TDP-43 de-mixing depletes nuclear TDP-43 and induces cell death Authors SUMMARY While cytoplasmic aggregation of TDP-43 is a pathological hallmark of amyotrophic lateral sclerosis and frontotemporal dementia, how aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
418
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(499 citation statements)
references
References 74 publications
(82 reference statements)
43
418
0
Order By: Relevance
“…However, in disease, heavily phosphorylated and ubiquitylated aggregates of TDP-43 accumulate cytoplasmically (20), accompanied by its nuclear clearance. We recently reported that TDP-43 naturally de-mixes in the nucleus, and shuttles to the cytoplasm in response to multiple stresses (21). Loss of nuclear TDP-43 causes usage of cryptic splice (22)(23)(24) and polyadenylation sites (24), dysregulating many important neuronal genes such as HDAC6 (25) and stathmin-2 (22,24).…”
Section: Mislocalization and Aggregation Of The Heterogeneous Nuclearmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in disease, heavily phosphorylated and ubiquitylated aggregates of TDP-43 accumulate cytoplasmically (20), accompanied by its nuclear clearance. We recently reported that TDP-43 naturally de-mixes in the nucleus, and shuttles to the cytoplasm in response to multiple stresses (21). Loss of nuclear TDP-43 causes usage of cryptic splice (22)(23)(24) and polyadenylation sites (24), dysregulating many important neuronal genes such as HDAC6 (25) and stathmin-2 (22,24).…”
Section: Mislocalization and Aggregation Of The Heterogeneous Nuclearmentioning
confidence: 99%
“…Recognizing earlier work demonstrating that endogenous TDP-43 naturally phase separates in several cell culture models and in the mouse nervous system (21) and that an RNA-binding deficient TDP-43 promotes phase separation and aggregation in multiple cellular models (27)(28)(29), we tested if interaction between RNA and TDP-43 regulates LLPS of intranuclear TDP-43. TDP-43 contains an N-terminal self-association domain (30,31), a C-terminal LCD, and two conserved RNA recognition motifs (RRM1 and RRM2) whose RNA-binding activity can be abolished by acetylation of two lysine residues (K145 in RRM1 and K192 in RRM2) (27).…”
Section: Rna Binding-deficient Tdp-43 De-mixes Into Ilsa In Physiologmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic details on the dynamics of such granules in TDP-43 pathophysiology remains unclear. However, many different proteins are known to interact with and partition into the phase separated droplets of TDP-43 (40,41). In FTLD and ALS, the aberrant LLPS of TDP-43 has emerged as a driving factor for the aggregation of the protein (40,42,43).…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of cellular stress, both TDP-43 and FUS re-localize into cytoplasmic stress granules (SGs) [6,7], which are dynamic mRNA-protein assemblies implicated in regulating mRNA function [8,9]. Given this, and in light of ALS-associated mutations that generally reduce SG dynamics, SGs have been theorized to promote formation of TDP-43 and FUS aggregates that are observed in ALS patients [10,11], though recent studies suggest SG-independent aggregation mechanism also likely exist [12][13] [14]. Regardless, various studies indicate that TDP-43 and FUS aggregates, or simply excessive cytoplasmic localization of TDP-43 or FUS, may result in a toxic gain of function that leads to motor-neuron degeneration [15][16][17][18][19] [20,21].…”
Section: Introductionmentioning
confidence: 99%